Assessing Community Readiness in Mojokerto toward Majapahit Marine Resort Development Plan - Hayati, Cucu; Lestari, Sri; Setyawan, Mochamad Ardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development and management of a program must involve the community, as well as the development of Majapahit Maritime Tourism. This community involvement aims to make the program development sustainable and improve welfare. This research is considered necessary as an initial measurement (assessment) of the readiness of the community in the Ngotok River Basin, Rejoto Bridge, Pulorejo Village, Prajurit Kulon District, Mojokerto City. The analysis is viewed from the socio-economic setting of the community, the readiness of stakeholders to face socio-economic changes, and the readiness to manage the Majapahit Marine Tourism village. The mixed method research method was chosen as an approach in answering research problems. The number of respondents in this study were 101 people who were selected by clustered random sampling. Data was collected by distributing semi-closed-end questionnaires, interviews with stakeholders determined by purposive sampling and field observations. Data analysis was carried out through descriptive analysis of cross tables (crosstabulation), weighting and review of several related spatial planning documents. Test the validity of the study using data triangulation. Regarding the development plan for Majapahit Maritime Tourism, this study concludes that the readiness of the Mojokerto community is at the Preparation stage. The pattern of community adaptation in responding to social, economic and environmental issues that are predicted to occur as a result of the development of Majapahit Maritime Tourism is categorized in adaptation by adjustment. Although Majapahit Maritime Tourism will only operate in 2023, policy makers have made physical, social and economic preparations in welcoming this development plan through the formation of Tourism Awareness Groups (Pokdarwis), program socialization through digital platforms, integration of coordination of program preparation by the government, government agencies. Sub-district to village government. It is hoped that all Mojokerto people can benefit from this tourism development.